Preparation method for accelerating densification of surface layer of hard carbon fiber thermal insulation material

By setting a graphene dense layer on the surface of the hard carbon fiber insulation material and sintering to form a ceramic-filled surface layer, the problem of insufficient oxidation performance of the hard carbon fiber insulation material at high temperatures is solved, and its wear resistance and mechanical properties are improved.

CN119553510APending Publication Date: 2025-03-04HENAN GUANHE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411744274.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing hard carbon fiber insulation materials have insufficient oxidation performance at high temperatures and have poor surface density, which affects their wear resistance and mechanical properties.

Method used

By providing a graphene dense layer on the surface of the hard carbon fiber substrate and sintering under a specific atmosphere, a densified surface layer containing titanium carbide, titanium nitride and titanium carbon nitride ceramic fill is formed.

Benefits of technology

It significantly improves the high-temperature oxidation resistance, wear resistance and mechanical properties of hard carbon fiber insulation materials, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a preparation method for accelerating densification of a surface layer of a hard carbon fiber thermal insulation material, which comprises the following steps: arranging a graphene compact layer on the surface of a hard carbon fiber base material, then applying a pretreatment solution containing titanate as a titanium source, and sintering in a specific atmosphere to prepare the hard carbon fiber thermal insulation material containing titanium carbide and titanium nitride, and the densified surface layer is filled with titanium carbonitride ceramic. The carbon fiber thermal insulation material prepared by the method has high-temperature oxidation resistance, meanwhile, the surface layer contains a ceramic material, so that the carbon fiber thermal insulation material also has relatively high wear resistance and relatively high mechanical property, and the preparation method disclosed by the invention simultaneously improves the mechanical property and prolongs the service life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal insulation materials, in particular to a preparation method for accelerating the densification of the surface layer of a hard carbon fiber thermal insulation material. Background Art

[0002] There are two types of carbon fiber insulation felt: soft carbon fiber insulation felt and hard carbon fiber insulation felt. The main difference between the two is whether the impregnation and curing treatment is carried out during the production process. Since the hard carbon fiber felt has a certain hardness and strength after impregnation and curing, it can support and work independently. Based on these advantages, hard carbon fiber insulation felt has gradually become the mainstream of carbon fiber insulation felt research and development at home and abroad. Carbon fiber hard felt is a product obtained after the carbon fiber soft felt has undergone an impregnation, curing and drying process. It can be processed into various shapes, is very convenient to install and disassemble, is resistant to oxidation and airflow erosion, has excellent thermal insulation effect, and has a long service life. A dense coating is provided on the surface of the hard fiber felt, so that the high temperature oxidation resistance of the hard fiber felt can be improved. The present invention provides a preparation method for accelerating the densification of the surface layer of a hard carbon fiber insulation material. Summary of the invention

[0003] The present invention relates to a preparation method for accelerating the densification of the surface layer of a hard carbon fiber thermal insulation material. The present invention first sets a graphene dense layer on the surface of a hard carbon fiber substrate, then applies a pretreatment solution containing titanate as a titanium source, and performs sintering treatment under a specific atmosphere to obtain a densified surface layer filled with titanium carbide, titanium nitride, and titanium carbonitride ceramics. The carbon fiber thermal insulation material prepared by the method has high-temperature oxidation resistance, and because the surface layer contains ceramic materials, it also has high wear resistance and high mechanical properties. The preparation method of the present invention also improves the mechanical properties and life of the material.

[0004] A preparation method for accelerating the densification of a surface layer of a rigid carbon fiber thermal insulation material, the method comprising:

[0005] 1) ultrasonically cleaning the hard carbon fiber felt substrate in ethanol, drying it, and then coating the epoxy resin adhesive on the surface of the substrate and drying it;

[0006] 2) applying a phenolic resin coating on the surface of the product in step 1 and drying, wherein the phenolic resin coating comprises: phenolic resin, graphene, silicon carbide fiber, fumed silica, and ethanol solvent;

[0007] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, sintering at high temperature, cooling to room temperature and taking out;

[0008] 4) coating the surface of the product obtained in step 3 with a surface coating and drying the surface coating, wherein the surface coating comprises: butyl titanate, γ-aminopropyltrimethylsilane, phenolic resin, modified silica particles, and ethanol solvent; the modified silica particles are prepared by the following method: mixing silica, zirconium dioxide, aluminum oxide, and magnesium oxide by ball milling, sintering, cold quenching, and ball milling to obtain the modified silica particles;

[0009] 5) placing the product obtained in step 4 in a tubular furnace, introducing nitrogen containing propylene, titanium tetrachloride and ammonia, heating and sintering to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0010] Furthermore, the phenolic resin coating comprises: 1.5-2 parts by mass of phenolic resin, 0.8-1.2 parts by mass of graphene, 0.4-0.6 parts by mass of silicon carbide short fibers, 0.05-0.08 parts by mass of fumed silica, and 4.0-6.0 parts by mass of ethanol solvent.

[0011] Furthermore, the nitrogen containing propylene and monosilane comprises 6-10% by volume of propylene, 15-20% by volume of monosilane, and the remainder being nitrogen.

[0012] Furthermore, the surface coating comprises: 1.0-1.2 parts by mass of butyl titanate, 4.0-4.8 parts by mass of γ-aminopropyltrimethylsilane, 1.5-2 parts by mass of phenolic resin, 1.0-1.5 parts by mass of modified silica particles, and 6.0-8.0 parts by mass of ethanol solvent.

[0013] Furthermore, the modified silica particles are prepared by the following method: 70-75 parts by mass of silica, 6-8 parts by mass of zirconium dioxide, 3-5 parts by mass of aluminum oxide, and 1-2 parts by mass of magnesium oxide are ball-milled and mixed, and then sintered at 1300-1400° C. for 3-6 hours, quenched in cold water at 0° C., and ball-milled to obtain the modified silica particles.

[0014] Furthermore, the nitrogen containing propylene, titanium tetrachloride and ammonia comprises, in volume percentage, 6-10% propylene, 6-10% titanium tetrachloride, 6-10% ammonia and the remainder nitrogen.

[0015] Furthermore, in step 5, the temperature is heated to 1600-1800° C. and maintained for 6-8 hours, and then the temperature is raised to 2200-2300° C. and maintained for 20-30 hours to obtain a hard carbon fiber thermal insulation material with a densified surface.

[0016] Furthermore, the material is prepared by the method described.

[0017] Beneficial technical effects of the present invention

[0018] 1) A graphene anti-corrosion layer is arranged on the surface of the hard carbon fiber. Graphene has a high melting point, high thermal stability, good physical and chemical compatibility with the hard carbon fiber felt, and an approximate expansion coefficient, and can play a positive role in high-temperature oxidation protection; at the same time, silicon carbide fiber is added to the layer to improve the crack resistance of the graphene layer;

[0019] 2) Epoxy resin adhesive is used to coat between the graphene layer and the carbon fiber matrix to prevent the graphene layer from penetrating into the interior of the hard carbon fiber and affecting its thermal insulation performance; during the carbonization process, nitrogen containing propylene and monosilane is introduced to generate silicon carbide at high temperature to fill the pores of the graphene layer, thereby improving the density of the coating;

[0020] 3) A dense surface structure is formed on the surface of the graphene layer, wherein butyl titanate, γ-aminopropyltrimethylsilane, phenolic resin, and modified silica particles in the surface coating can generate ceramic materials such as silicon carbide and titanium carbide under the action of high temperature, and at the same time, glass phase silica and aluminum oxide can form mullite phase materials at high temperature, thereby filling cracks or gaps in the surface layer and improving the density of the surface layer. At the same time, during the sintering process, by adding propylene, titanium tetrachloride, and ammonia, titanium nitride, titanium carbide, and titanium carbonitride ceramics can be formed in the pores of the surface layer, thereby improving the density and wear resistance of the surface layer. DETAILED DESCRIPTION

[0021] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0022] Example 1

[0023] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0024] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 1.5 parts by mass of phenolic resin, 0.8 parts by mass of graphene, 0.4 parts by mass of silicon carbide fiber, 0.05 parts by mass of fumed silica, and 4.0 parts by mass of ethanol solvent;

[0025] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, wherein the volume percentages are 6 volume percent propylene, 15 volume percent monosilane, and the balance is nitrogen, heating to 1000° C., maintaining for 12 hours, cooling to room temperature and taking out;

[0026] 4) Apply the surface coating to the surface of the product obtained in step 3, with a coating amount of 2.0 kg / m2 , dried, the surface coating comprises: 1.0 parts by mass of butyl titanate, 4.0 parts by mass of γ-aminopropyltrimethylsilane, 1.5 parts by mass of phenolic resin, 1.0 parts by mass of modified silica particles, and 6.0 parts by mass of ethanol solvent; the modified silica particles are prepared by the following method: 70 parts by mass of silica, 6 parts by mass of zirconium dioxide, 3 parts by mass of aluminum oxide, and 1 part by mass of magnesium oxide are ball-milled and mixed, and then sintered at 1300°C for 6h, quenched in cold water at 0°C, and ball-milled to obtain the modified silica particles;

[0027] 5) The product obtained in step 4 is placed in a tubular furnace, and nitrogen containing propylene, titanium tetrachloride, and ammonia is introduced, wherein the volume percentages are 6 volume percent propylene, 6 volume percent titanium tetrachloride, 6 volume percent ammonia, and the remainder is nitrogen; heated to 1600° C., maintained for 8 hours, and then heated to 2200° C., maintained for 30 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0028] Example 2

[0029] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0030] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 2 parts by mass of phenolic resin, 1.2 parts by mass of graphene, 0.6 parts by mass of silicon carbide fiber, 0.08 parts by mass of fumed silica, and 6.0 parts by mass of ethanol solvent;

[0031] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, wherein the volume percentage is 10 volume propylene, 20 volume silane, and the balance is nitrogen, heating to 1200° C., maintaining for 8 hours, cooling to room temperature and taking out;

[0032] 4) Apply the surface coating to the surface of the product obtained in step 3, with a coating amount of 2.0 kg / m 2 , dried, the surface coating comprises: 1.2 parts by mass of butyl titanate, 4.8 parts by mass of γ-aminopropyltrimethylsilane, 2 parts by mass of phenolic resin, 1.5 parts by mass of modified silica particles, and 8.0 parts by mass of ethanol solvent; the modified silica particles are prepared by the following method: 75 parts by mass of silica, 8 parts by mass of zirconium dioxide, 5 parts by mass of aluminum oxide, and 2 parts by mass of magnesium oxide are ball-milled and mixed, and then sintered at 1400°C for 3h, quenched in cold water at 0°C, and ball-milled to obtain the modified silica particles;

[0033] 5) The product obtained in step 4 is placed in a tubular furnace, and nitrogen containing propylene, titanium tetrachloride, and ammonia is introduced, wherein the volume percentages are 10 volume propylene, 10 volume titanium tetrachloride, 10 volume ammonia, and the balance is nitrogen; heated to 1800° C., maintained for 6 hours, and then heated to 2300° C., maintained for 20 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0034] Example 3

[0035] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0036] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 1.8 parts by mass of phenolic resin, 1 part by mass of graphene, 0.5 parts by mass of silicon carbide fiber, 0.06 parts by mass of fumed silica, and 5 parts by mass of ethanol solvent;

[0037] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, wherein the volume percentage is 8 volume percent propylene, 18 volume percent monosilane, and the balance is nitrogen, heating to 1100° C., maintaining for 10 hours, cooling to room temperature and taking out;

[0038] 4) Apply the surface coating to the surface of the product obtained in step 3, with a coating amount of 2.0 kg / m 2 , dried, the surface coating comprises: 1.1 parts by mass of butyl titanate, 4.4 parts by mass of γ-aminopropyltrimethylsilane, 1.8 parts by mass of phenolic resin, 1.2 parts by mass of modified silica particles, and 7 parts by mass of ethanol solvent; the modified silica particles are prepared by the following method: 72 parts by mass of silica, 7 parts by mass of zirconium dioxide, 4 parts by mass of aluminum oxide, and 1.5 parts by mass of magnesium oxide are ball-milled and mixed, sintered at 1350°C for 5h, quenched in cold water at 0°C, and ball-milled to obtain the modified silica particles;

[0039] 5) The product obtained in step 4 is placed in a tubular furnace, and nitrogen containing propylene, titanium tetrachloride, and ammonia is introduced, wherein the volume percentages are 8 volume percent of propylene, 8 volume percent of titanium tetrachloride, 8 volume percent of ammonia, and the balance is nitrogen; heated to 1700° C., maintained for 7 hours, and then heated to 2250° C., maintained for 25 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0040] Comparative Example 1 (graphene layer not provided)

[0041] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0042] 2) Apply the surface coating to the surface of the product obtained in step 1, with a coating amount of 2.0 kg / m 2 , dried, the surface coating comprises: 1.1 parts by mass of butyl titanate, 4.4 parts by mass of γ-aminopropyltrimethylsilane, 1.8 parts by mass of phenolic resin, 1.2 parts by mass of modified silica particles, and 7 parts by mass of ethanol solvent; the modified silica particles are prepared by the following method: 72 parts by mass of silica, 7 parts by mass of zirconium dioxide, 4 parts by mass of aluminum oxide, and 1.5 parts by mass of magnesium oxide are ball-milled and mixed, sintered at 1350°C for 5h, quenched in cold water at 0°C, and ball-milled to obtain the modified silica particles;

[0043] 3) placing the product obtained in step 2 in a tubular furnace, introducing nitrogen containing propylene, titanium tetrachloride, and ammonia, wherein the volume percentages are 8 volume percent of propylene, 8 volume percent of titanium tetrachloride, 8 volume percent of ammonia, and the remainder is nitrogen; heating to 1700° C., maintaining for 7 hours, and then heating to 2250° C., maintaining for 25 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0044] Comparative Example 2 (no surface dense layer)

[0045] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0046] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 1.8 parts by mass of phenolic resin, 1 part by mass of graphene, 0.5 parts by mass of silicon carbide fiber, 0.06 parts by mass of fumed silica, and 5 parts by mass of ethanol solvent;

[0047] 3) The product obtained in step 2 is placed in a tubular furnace, and nitrogen containing propylene and monosilane is introduced, wherein the volume percentage is 8 volume % of propylene and 18 volume % of monosilane, and the balance is nitrogen. The mixture is heated to 1100° C. and maintained for 10 hours. The mixture is cooled to room temperature and taken out to obtain a hard carbon fiber thermal insulation material.

[0048] Comparative Example 3 (No Epoxy Resin Layer Was Set)

[0049] 1) ultrasonically cleaning the hard carbon fiber felt substrate in ethanol for 30 minutes and drying;

[0050] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 1.8 parts by mass of phenolic resin, 1 part by mass of graphene, 0.5 parts by mass of silicon carbide fiber, 0.06 parts by mass of fumed silica, and 5 parts by mass of ethanol solvent;

[0051] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, wherein the volume percentage is 8 volume percent propylene, 18 volume percent monosilane, and the balance is nitrogen, heating to 1100° C., maintaining for 10 hours, cooling to room temperature and taking out;

[0052] 4) Apply the surface coating to the surface of the product obtained in step 3, with a coating amount of 2.0 kg / m 2 , dried, the surface coating comprises: 1.1 parts by mass of butyl titanate, 4.4 parts by mass of γ-aminopropyltrimethylsilane, 1.8 parts by mass of phenolic resin, 1.2 parts by mass of modified silica particles, and 7 parts by mass of ethanol solvent; the modified silica particles are prepared by the following method: 72 parts by mass of silica, 7 parts by mass of zirconium dioxide, 4 parts by mass of aluminum oxide, and 1.5 parts by mass of magnesium oxide are ball-milled and mixed, sintered at 1350°C for 5h, quenched in cold water at 0°C, and ball-milled to obtain the modified silica particles;

[0053] 5) The product obtained in step 4 is placed in a tubular furnace, and nitrogen containing propylene, titanium tetrachloride, and ammonia is introduced, wherein the volume percentages are 8 volume percent of propylene, 8 volume percent of titanium tetrachloride, 8 volume percent of ammonia, and the balance is nitrogen; heated to 1700° C., maintained for 7 hours, and then heated to 2250° C., maintained for 25 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0054] Comparative Example 4 (Sintering atmosphere is nitrogen)

[0055] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0056] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 1.8 parts by mass of phenolic resin, 1 part by mass of graphene, 0.5 parts by mass of silicon carbide fiber, 0.06 parts by mass of fumed silica, and 5 parts by mass of ethanol solvent;

[0057] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen, heating to 1100° C., maintaining for 10 h, cooling to room temperature and taking out;

[0058] 4) Apply the surface coating to the surface of the product obtained in step 3, with a coating amount of 2.0 kg / m 2 , dried, the surface coating comprises: 1.1 parts by mass of butyl titanate, 4.4 parts by mass of γ-aminopropyltrimethylsilane, 1.8 parts by mass of phenolic resin, 1.2 parts by mass of modified silica particles, and 7 parts by mass of ethanol solvent; the modified silica particles are prepared by the following method: 72 parts by mass of silica, 7 parts by mass of zirconium dioxide, 4 parts by mass of aluminum oxide, and 1.5 parts by mass of magnesium oxide are ball-milled and mixed, sintered at 1350°C for 5h, quenched in cold water at 0°C, and ball-milled to obtain the modified silica particles;

[0059] 5) placing the product obtained in step 4 in a tubular furnace and introducing nitrogen; heating to 1700° C., maintaining for 7 hours, and then raising the temperature to 2250° C., maintaining for 25 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0060] Comparative Example 5 (modified silica not added to the surface layer)

[0061] 1) The rigid carbon fiber felt substrate was ultrasonically cleaned in ethanol for 30 min, dried, and then the epoxy resin adhesive was coated on the substrate surface with a coating amount of 0.6 kg / m 2 ,dry;

[0062] 2) Apply phenolic resin coating on the surface of the product in step 1, with a coating amount of 6.0 kg / m 2 , drying, the phenolic resin coating comprises: 1.8 parts by mass of phenolic resin, 1 part by mass of graphene, 0.5 parts by mass of silicon carbide fiber, 0.06 parts by mass of fumed silica, and 5 parts by mass of ethanol solvent;

[0063] 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, wherein the volume percentage is 8 volume percent propylene, 18 volume percent monosilane, and the balance is nitrogen, heating to 1100° C., maintaining for 10 hours, cooling to room temperature and taking out;

[0064] 4) Apply the surface coating to the surface of the product obtained in step 3, with a coating amount of 2.0 kg / m 2 , dried, the surface coating comprising: 1.1 parts by mass of butyl titanate, 4.4 parts by mass of γ-aminopropyltrimethylsilane, 1.8 parts by mass of phenolic resin, and 7 parts by mass of ethanol solvent;

[0065] 5) The product obtained in step 4 is placed in a tubular furnace, and nitrogen containing propylene, titanium tetrachloride, and ammonia is introduced, wherein the volume percentages are 8 volume percent of propylene, 8 volume percent of titanium tetrachloride, 8 volume percent of ammonia, and the balance is nitrogen; heated to 1700° C., maintained for 7 hours, and then heated to 2250° C., maintained for 25 hours, to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

[0066] Test Data

[0067] The product performance of the embodiments of the present invention and the comparative examples was tested, and the results are shown in Table 1. After oxidation in air at 1200°C for 72 hours, the samples were weighed and the weight loss rate was calculated. The weight loss rate of the samples can be used to measure the density of the coating. The denser the coating, the fewer cracks at high temperature, and the lower the weight loss rate in an oxidizing environment, and vice versa.

[0068] Table 1

[0069]

[0070]

[0071] It can be seen from the embodiments and comparative examples that from comparative examples 1 and 2, the dense layer and the graphene layer have different influences on thermal weight loss, and the dense layer has the greatest influence on thermal weight loss. From comparative examples 3 and 4, the influence of the epoxy resin layer and the sintering atmosphere can be seen, and from comparative example 5, the role of modified silicon dioxide in the dense layer. By comparing the processes of the embodiments and comparative examples of the present invention, it can be seen that the graphene anti-corrosion layer is set on the surface of the hard carbon fiber, which can play a positive role in high-temperature oxidation protection; epoxy resin adhesive is used between the graphene layer and the carbon fiber matrix to prevent the graphene layer from penetrating into the interior of the hard carbon fiber and affecting its thermal insulation performance; during the carbonization process, nitrogen containing propylene and monosilane is introduced, and silicon carbide is generated at high temperature to fill the pores of the graphene layer to improve the density of the coating; during the sintering of the surface layer, by adding propylene, titanium tetrachloride, and ammonia, titanium nitride, titanium carbide and titanium carbonitride ceramics can be formed in the pores of the surface layer to improve the density of the surface layer. The modified silica particles in the surface coating can form mullite phase materials under the action of high temperature, thereby filling the cracks or gaps in the surface and improving the density of the surface.

[0072] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.

Claims

1. A preparation method for accelerating the densification of the surface layer of a rigid carbon fiber thermal insulation material, characterized in that: The method comprises: 1) ultrasonically cleaning the hard carbon fiber felt substrate in ethanol, drying it, and then coating the epoxy resin adhesive on the surface of the substrate and drying it; 2) applying a phenolic resin coating on the surface of the product in step 1 and drying, wherein the phenolic resin coating comprises: phenolic resin, graphene, silicon carbide fiber, fumed silica, and ethanol solvent; 3) placing the product obtained in step 2 in a tube furnace, introducing nitrogen containing propylene and monosilane, sintering at high temperature, cooling to room temperature and taking out; 4) coating the surface of the product obtained in step 3 with a surface coating and drying the surface coating, wherein the surface coating comprises: butyl titanate, γ-aminopropyltrimethylsilane, phenolic resin, modified silica particles, and ethanol solvent; the modified silica particles are prepared by the following method: mixing silica, zirconium dioxide, aluminum oxide, and magnesium oxide by ball milling, sintering, cold quenching, and ball milling to obtain the modified silica particles; 5) placing the product obtained in step 4 in a tubular furnace, introducing nitrogen containing propylene, titanium tetrachloride and ammonia, heating and sintering to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

2. The preparation method according to claim 1, characterized in that: The phenolic resin coating comprises: 1.5-2 parts by mass of phenolic resin, 0.8-1.2 parts by mass of graphene, 0.4-0.6 parts by mass of silicon carbide short fibers, 0.05-0.08 parts by mass of fumed silica, and 4.0-6.0 parts by mass of ethanol solvent.

3. The preparation method according to claim 1, characterized in that: The nitrogen containing propylene and monosilane comprises 6-10% by volume of propylene, 15-20% by volume of monosilane, and the remainder being nitrogen.

4. The preparation method according to claim 1, characterized in that: The surface coating comprises: 1.0-1.2 parts by mass of butyl titanate, 4.0-4.8 parts by mass of γ-aminopropyltrimethylsilane, 1.5-2 parts by mass of phenolic resin, 1.0-1.5 parts by mass of modified silicon dioxide particles, and 6.0-8.0 parts by mass of ethanol solvent.

5. The preparation method according to claim 4, characterized in that: The modified silicon dioxide particles are prepared by the following method: 70-75 parts by mass of silicon dioxide, 6-8 parts by mass of zirconium dioxide, 3-5 parts by mass of aluminum oxide, and 1-2 parts by mass of magnesium oxide are ball-milled and mixed, and then sintered at 1300-1400° C. for 3-6 hours, quenched in cold water at 0° C., and ball-milled to obtain the modified silicon dioxide particles.

6. The preparation method according to claim 1, characterized in that: The nitrogen containing propylene, titanium tetrachloride and ammonia comprises 6-10% by volume of propylene, 6-10% by volume of titanium tetrachloride, 6-10% by volume of ammonia and the remainder being nitrogen.

7. The preparation method according to claim 1, characterized in that: In the step 5, the temperature is heated to 1600-1800° C. and maintained for 6-8 hours, and then the temperature is raised to 2200-2300° C. and maintained for 20-30 hours to obtain a hard carbon fiber thermal insulation material with a densified surface layer.

8. A hard carbon fiber thermal insulation material with a densified surface, characterized in that: The material is prepared by the method according to any one of claims 1 to 7.